MEMBANGUN STRATEGI MISI KONTEKSTUAL BAGI GENERASI MILENIAL MEMANFAATKAN METAVERSE - Hutabarat, Samuel; Lie, Romi (Sekolah Tinggi Teologi Injili Abdi Allah, 2023)
ABSTRACT:MetaVerse is a new technology in the virtual world that is developing rapidly and is believed to be (or has) become part of the new life of the world community (especially the millennial generation). This technology must be addressed carefully by the church. This article examines how to build a contextual mission strategy for the millennial generation by utilizing MetaVerse technology. This research was conducted through the method of reviewing books, journals, articles, information and data related to the topic. The analysis is carried out by examining how the church can conduct a mission in the MetaVerse, the importance of missionary service to the millennial generation, and whether worship in the MetaVerse will provide the same spiritual experience as worship in the real world. The result of the analysis is that MetaVerse is not a threat to the church but should be seen as a new field of evangelism where there is an opportunity to reach the millennial generation.Key Words: MetaVerse, millennial, mission, contextual, virtual.ABSTRAK: MetaVerse adalah teknologi baru dalam dunia virtual yang sedang berkembang dengan cepat dan dipercaya akan (atau sudah) menjadi bagian dari kehidupan baru masyarakat dunia (terlebih lagi generasi milenial). Teknologi ini harus disikapi dengan cermat oleh gereja. Artikel ini mengkaji bagaimana cara membangun strategi misi kontekstual bagi generasi milenial dengan memanfaatkan teknologi MetaVerse. Penelitian ini dilakukan melalui metode penelahaan atas buku, jurnal, artikel, informasi dan data yang berhubungan dengan topik. Analisis dilakukan dengan mengkaji bagaimana gereja bisa bermisi di MetaVerse, pentingnya pelayanan misi ke generasi milenial, dan apakah ibadah dalam MetaVerse akan memberi pengalaman rohani yang sama dengan ibadah dalam dunia nyata. Hasil analisa adalah MetaVerse bukanlah ancaman bagi gereja melainkan harus dilihat sebagai ladang penginjilan baru dimana ada kesempatan untuk menjangkau generasi milenial.Kata Kunci: MetaVerse, milenial, misi, kontekstual, virtual.ABSTRACT:MetaVerse is a new technology in the virtual world that is developing rapidly and is believed to be (or has) become part of the new life of the world community (especially the millennial generation). This technology must be addressed carefully by the church. This article examines how to build a contextual mission strategy for the millennial generation by utilizing MetaVerse technology. This research was conducted through the method of reviewing books, journals, articles, information and data related to the topic. The analysis is carried out by examining how the church can conduct a mission in the MetaVerse, the importance of missionary service to the millennial generation, and whether worship in the MetaVerse will provide the same spiritual experience as worship in the real world. The result of the analysis is that MetaVerse is not a threat to the church but should be seen as a new field of evangelism where there is an opportunity to reach the millennial generation.